Biomimetic anisotropic polymeric nanoparticles coated with red blood cell membranes for enhanced circulation and toxin removal - Ben-Akiva, Elana (Sci Adv, 2020)
The design of next-generation nanobiomaterials requires precise engineering of both physical properties of the core material and chemical properties of the material’s surface to meet a biological function. A bio-inspired modular and versatile technology was developed to allow biodegradable polymeric nanoparticles to circulate through the blood for extended periods of time while also acting as a detoxification device. To mimic red blood cells, physical and chemical biomimicry are combined to enhance the biological function of nanomaterials in vitro and in vivo. The anisotropic shape and membrane coating synergize to resist cellular uptake and reduce clearance from the blood. This approach enhances the detoxification properties of nanoparticles, markedly improving survival in a mouse model of sepsis. The anisotropic membrane-coated nanoparticles have enhanced biodistribution and therapeutic efficacy. These biomimetic biodegradable nanodevices and their derivatives have promise for applications ranging from detoxification agents, to drug delivery vehicles, and to biological sensors.